Effect of Openings on the Performance of Continuous RC One-Way Slabs - Al-Quraishy, Nameer M. Jawad; Alrudaini, Thaer M. Saeed; lafta, Yousif J. (Engineering, Technology & Applied Science Research, 2025)
Nowadays, slab openings have become necessary for service purposes in most new and old constructions, therefore, their effect on the slab strength should be extensively investigated. This paper explores the effect of such openings on the performance of a one-way continuous Reinforced Concrete (RC) slab. Fourteen slabs with different opening categories were cast. The main parameters studied in this research were the opening size, opening location, and slab thickness. The study focused on two span slabs, including openings with and without the proposed diagonal reinforcement at the corners. All slabs had identical spans and widths whereas two thicknesses were used. Openings of varying sizes were introduced at different locations within the spans. The results indicate a significant reduction in load capacity and ductility for the slabs with openings. The largest reduction occurred when the largest opening was placed near the mid-support, resulting in a 21.3% decrease in load capacity. Conversely, the smallest reduction was observed in the slab with the same large opening but with additional reinforcement, resulting in only a 1.74% decrease in load capacity.